ANALYSIS OF PARENT-TEACHER COOPERATION IN INCREASING LEARNING MOTIVATION GRADE III STUDENTS OF ASDU PRIVATE ISLAMIC ELEMENTARY SCHOOL TANGERANG REGENCY - Dina Erika Septiana; Sunardin; Yeni Nuraeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is entitled "Analysis of Parent-Teacher Cooperation in Increasing the Learning Motivation of Grade III Students of ASDU Private Islamic Elementary School, Tangerang Regency." This study aims to find out the form of cooperation carried out by parents and teachers in increasing the learning motivation of grade III students. This study uses a qualitative descriptive method with subjects consisting of classroom teachers, guardians, and grade III students. The research was conducted at the ASDU Private Islamic Elementary School, Tangerang Regency, in 2024. The data collection techniques used include observation, interviews, and documentation studies. Data reduction techniques, presentation, and conclusions are used to analyze the data. The study results show that cooperation between parents and teachers in learning activities includes creating communication groups and forums that students' guardians routinely attend. In addition, collaboration outside of learning activities is shown through liaison books to monitor student activities and encourage children to engage in positive activities outside of study hours, such as extracurricular activities. This result is expected to increase students' overall learning motivation.